Somatization symptomology and its association with stress in patients with irritable bowel syndrome - Saira Akhlaq; Nosheen Kazmi; Syed Murtaza Hassan Kazmi; Muslim Atiq; Sajawal Hussain; Ahmed Bajwa; Abdul Ahad; Muhammad Yaqoob Akhtar; Kalsoom Akhlaq; Mohammad Rizwan (PLoS ONE, 2025)
Irritable Bowel Syndrome (IBS) patients and Somatization Symptom Disorder (SSD) patients experience somatization symptoms relative to their corresponding processes. IBS patients may also have a diagnosis of both IBS and SSD. Somatization symptoms cause significant psychological, emotional and social distress. Conversely, stress in any form is believed to contribute to IBS symptoms. Whether stress mediated somatization symptoms in patients with IBS provide a pathway for these IBS symptoms is not as well understood. This cross-sectional study was performed at Shifa International Hospital, Islamabad between March 1st, 2023, and January 14th, 2024. Purposeful sampling was done to recruit study participants from three different populations as somatization is common in all three populations. As a result, there were three different samples in the study. Participants were eligible to participate if they had a diagnosis of IBS, somatic symptom disorder (SSD), or IBS with somatization (IBS-SSD) and were currently receiving treatment at the gastroenterology outpatient clinic and/or psychiatric outpatient clinic. Patient Health Questionnaire (PHQ-15) and Somatic Stress Response Scale (SSRS) were used to assess somatic symptoms and their association of stress-related somatic symptoms. Data was entered and analyzed using descriptive and inferential statistics. Data was self-reported by the participants. The largest sample size 67(100%) was from the IBS patient population. Two other samples were small i.e., there were 21 (100%) participants in SSD sample, and a very few numbers of participants 12 (100%) in the IBS diagnosis with a comorbidity of SSD sample. Majority of the patients were young i.e., 50≤ (77.7%), (71.4%), (74.99%); and male (59.7%), (66.6%), (50.0%) from the IBS, SSD, and IBS-SSD samples. Majority of the participants in the IBS (56.7%) and SSD (61.9%) samples had a high school diploma or the equivalent. In the IBS-SSD sample, the largest percentage (41.7%) of participants had more than a bachelor’s degrees. M = 85.67 (+/-23.26) for SSRS scores and M = 17.81(+/-5.28) for PHQ-15 scores in SSD patients. M = 75.21 (+/-19.59) for SSRS scores and M = 14.76 (+/-5.07) for PHQ-15 scores in IBS patients. M = 75.17 (+/-20.55) for SSRS scores and M = 14.92 (+/-6.27) for PHQ-15 scores in IBS-SSD patients. Many participants had somatization symptoms in the severe range (≥ 15) i.e., 34(50.7%), 17(81.0%), 6(50.0%) in IBS, SSD, and IBS-SSD samples respectively. Considering the PHQ scores by age in the IBS sample, highest mean scores were observed for the highest age group (60–69 years) i.e., 16.50 (+/- 5.68) despite fewer number of participants in this age group. PHQ scores also significantly differed by education groups i.e., significant differences were observed between education group 1 and 2 as well as group 2 and 3, p<0.05. On simple linear regression, PHQ-15 scores significantly predicted variations in SSRS scores, p <0.05, R2 = 69.6% for IBS sample, R2 = 68.7% for the SSD sample, and R2 = 66.0% for patients with IBS, SSD and IBS with somatization respectively. Stress related somatic symptoms are positively correlated with somatization complaints in IBS patients. Increased somatization scores were observed in the elderly. Targeted psycho-social interventions could help mitigate the negative effects of somatization in IBS patients.